Destination Image, Perceived Value, and Overall Satisfaction: An Application in Douala-Cameroon - Hieng, Progres Younda Ngo (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This work complement the study made by previous researchers on destination image who investigated precisely the relationship between destination image, perceived value, and overall satisfaction. Made in Douala-Cameroon, the particularity of this work reside on the fact that there is an implication for the local people (residents of this city). The result of this research shows that destination image is positively linked to perceive value; destination image and overall satisfaction are positively linked; then perceive value plays the role of a mediator between destination image and overall satisfaction. Some implications were mention but the most critical ones were focus on the government, the private sectors, and the local residents in issues such as the protection of goods and services, trust, and fairness if Douala-Cameroon is to be one of the best destination to visit in Cameroon and why not in the entire Africa. Keywords: Destination image; Perceived value; Overall Satisfaction; Cameroon; Douala.

ÖZ: Bu çalışma tam olarak algılanan değer, genel memnuniyet ve hedef görüntü arasındaki ilişki araştırıldı ayrıca görüntü üzerinde önceki araştırmacılar tarafından yapılan çalışmayı tamamlayacak. Kamerun da yapılan bu çalışma özelliği yerel halk için bir anlamı var, öyle ki (bu şehrin sakinleri) üzerinde bulunur. Bu araştırmanın sonucunda gösterir ki hedef görüntüsü olumlu şekilde bağlantılıdır algılanan değerle birlikte bu da olumlu olarak etkilidir genel memnuniyet değerleriyle. Douala-Kameron'un tüm Afrika'da değil, Kameron'daki en iyi ziyaret noktalarından biri olması için bazı sonuçlardan bahsedildi ama en kritik olanları devlete odaklananlardı; özel sektörler ve yerel halk, mallar ve hizmetlerin korunması, güven ve adalet konuları. Anahtar Kelimeler: Hedef Görüntü; Algılanan değer; Genel memnuniyet; Kamerun; Douala
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2015. Supervisor: Assist. Prof. Dr. Rüçhan Kayaman.
Keywords: Tourism; Tourism - Cameroon; Destination image; Perceived value; Overall Satisfaction; Cameroon; Douala